A simple method to isolate mutants in repressible cyclic phosphodiesterase in Neurospora crassa - K. Hasunuma (Fungal Genetics Reports, 1984)
A simple method to isolate mutants in repressible cyclic phosphodiesterase in Neurospora crassa.